2011
DOI: 10.1089/jmf.2010.0097
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant and Antiacetylcholinesterase Properties of Honeys from Different Floral Origins

Abstract: Twenty-three honey samples of Apis mellifera L. forged on plants from northeastern Brazil were analyzed to determine total phenolic content, flavonoid content, antioxidant activity, and antiacetylcholinesterase activity. The total phenol content was determined by using the Folin-Ciocalteu method, and the flavonoid content was analyzed using by the aluminum chloride method. The antioxidant activity was evaluated using the diphenyl-1-picrylhydrazyl-scavenging test. Honey samples from Lippia sidoides Cham. (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
3
18
1
5
Order By: Relevance
“…In addition, Beretta et al, (2005) showed some values on unifloral and multifloral honey samples of Africa (52.2 to 789.6 mg/kg) and Bertoncelj et al (2007) on Slovakia honey samples (64 to 1304 µgGAE/g). Also, values raging between 226.2 and 727.8 mg/kg were reported in Portugal (Ferreira et al, 2009) and from 102.1 to 1085 mg/kg in the north-east of Brazil (Liberato et al, 2011). The main explanation for this difference could be linked to the unequal distribution of polyphenols both in quantity and quality across the different organs of a plant used by bees to produce honey.The amount of flavonoids in the samples collected in rainy (280 ± 31 µgCE/g) and dry seasons (528 ± 31 µgCE/g) displays a great variability within seasons (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Beretta et al, (2005) showed some values on unifloral and multifloral honey samples of Africa (52.2 to 789.6 mg/kg) and Bertoncelj et al (2007) on Slovakia honey samples (64 to 1304 µgGAE/g). Also, values raging between 226.2 and 727.8 mg/kg were reported in Portugal (Ferreira et al, 2009) and from 102.1 to 1085 mg/kg in the north-east of Brazil (Liberato et al, 2011). The main explanation for this difference could be linked to the unequal distribution of polyphenols both in quantity and quality across the different organs of a plant used by bees to produce honey.The amount of flavonoids in the samples collected in rainy (280 ± 31 µgCE/g) and dry seasons (528 ± 31 µgCE/g) displays a great variability within seasons (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The coriander and mustard honey contained very small amount of ash (Table 1) as compare to Nigeria honey [28] acacia, sunflower, lime and multi flora honey [15].…”
Section: Ash Contentmentioning
confidence: 97%
“…Estos valores son comparables con los hallados en mieles portuguesas y africanas, con 226.2 a 727.8 y 52.2 a 789.6 (mg kg -1 A. Gálico), 50 aunque se conocen otros estudios donde el parámetro oscila entre 102.1 a 1085 mg kg -1 . 61 El tenor de fenoles de la miel de Encenillo es indicador de una importante actividad antioxidante total (AAT).…”
Section: Propiedades Generalesunclassified